Single nucleotide variants and indels identified from whole-genome resequencing of Gyr, Girolando, and Holstein cattle breeds. - STAFUZZA, N. B. (2017)
Edição dos abstracts do Breeding and Genetics Symposium, Baltimore, 2017.